COMPARISON OF THE EFFECTIVENESS OF ANTIMICOTIC EXTRACT OF ETHANOL TEMU KUNCI AND TEMULAWAK ON CANDIDA ALBICANS - Ekaristy, Mergivia; Novita, Bernadette Dian; Angelina, Zenia (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Candida albicans are normal flora bacteria on the skin and mucous membranesof humans. Candida albicans are said to be one of the causes of vaginal discharge or fluoralbus. Temu kunci (Boesenbergia pandurata (Roxb.) Schlect) and temulawak (Curcumaxanthorrhiza Roxb) are the ingredients of herbal medicines with the potential as anantifungal. Purpose: This study aims to explain the differences in the antifungal effect of the Temukunci (Boesenbergia pandurata (Roxb.) Schlect) and Temulawak (Curcuma xanthorrhizaRoxb) extracts and explain how the combination of Temu kunci (Boesenbergia pandurata(Roxb.) Schlect) and Temulawak (Curcuma xanthorrhiza Roxb) extracts has an antifungaleffect on Candida albicans by using the experimental study of post-test control group design. Method: This study uses the Kirby-Baurer method and then measures the inhibitory zone byusing calipers then comparing the inhibition zone of each extract. Results: The research results show no difference in the effectiveness of each extract, and noinhibition zone was found for each extract. Conclusion: This study concludes that the two extracts are not effective against C.albicans.